Penerapan Hukum Keimigrasian Pada Perbatasan Negara di Daerah Terpencil Kaitannya Dengan Teori Ruang Berada - Zulfikar, Mohammad (UNES Law Review, 2024)
The application of Immigration Law is carried out in the implementation of immigration checking at Immigration Checkpoints for every person entering or leaving Indonesian territory in order to maintain the upholding of state sovereignty. Immigration checks are carried out by checking travel documents and visas or residence permits as well as checking the preventive and wanted list. Immigration checking at Immigration Checkpoints, such as at airports, harbors, and border crossing posts, are carried out by checking data on people entering or leaving Indonesian territory according to their travel documents and/or visas on the Immigration Management Information System. However, carrying out immigration inspections in accordance with Immigration Law and regulations is difficult to be implemented in remote areas which locations are difficult to reach from urban areas, making it difficult to carry out immigration inspections in accordance with applicable regulations. This is because of the lack of transportation and network are still difficult, making it difficult to connect the Immigration Management Information System. Apart from that, in several border areas where indigenous people live side by side with neighboring countries, they often go in and out of the country's borders in order to carry out daily activities, such as school, trading, work, family visits, and other activities, so if indigenous people around the border must use passport as a travel document for entering and exiting the territory of Indonesia, will burden the community to pay the Non-Tax State Revenue fees for applying for a passport due to the activities of the community who enter and exit the territory of Indonesia every day, whereas the Passport book only has 48 (forty eight) pages, and there are only 42 (forty two) visa pages available to display departure and arrival stamps. In this article, we will discuss further how the Government, in this case the Directorate General of Immigration, Ministry of Law and Human Rights, implements the application of immigration law in remote areas in relation to the Theory of Existing Space and how the Directorate General of Immigration, Ministry of Law and Human Rights, can form regulations or policies. which can accommodate people in border areas that are categorized as Private Spaces.